2013
DOI: 10.5664/jcsm.3266
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Daytime Sleepiness is Associated with Longer Culprit Lesion and Adverse Outcomes in Patients with Coronary Artery Disease

Abstract: In patients presenting with coronary artery disease, excessive daytime sleepiness based on ESS > 10 was associated with longer culprit lesions and future adverse cardiovascular events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 26 publications
1
10
1
3
Order By: Relevance
“…As an easily recognized complaint, EDS can be readily incorporated into routine evaluations for patients receiving secondary prevention therapy after MI. The prognostic value of EDS in post-MI patients is a novel finding and is consistent with previous studies in non-MI patients, [5][6][7] although other investigations did not report significant correlation of EDS with CVD prevalence in a cross-sectional study 20 or incidence of new-onset CVD in longitudinal observation. 21 A number of factors have been hypothesized as accounting for the unfavorable cardiovascular profile in sleepy individuals.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As an easily recognized complaint, EDS can be readily incorporated into routine evaluations for patients receiving secondary prevention therapy after MI. The prognostic value of EDS in post-MI patients is a novel finding and is consistent with previous studies in non-MI patients, [5][6][7] although other investigations did not report significant correlation of EDS with CVD prevalence in a cross-sectional study 20 or incidence of new-onset CVD in longitudinal observation. 21 A number of factors have been hypothesized as accounting for the unfavorable cardiovascular profile in sleepy individuals.…”
Section: Discussionsupporting
confidence: 90%
“…Excessive daytime sleepiness (EDS) is a common symptom in patients with SDB and has been associated with an increased risk of motor vehicle accidents, occupational injuries, and the development of cerebrovascular diseases and CVD 3, 4. Moreover, longitudinal studies have shown that EDS is an independent risk factor for adverse outcomes in patients with coronary artery disease5 and predicts cardiovascular mortality 6, 7. Although continuous positive airway pressure (CPAP) is recommended for patients with moderate to severe SDB,8 evidence for its use in SDB patients with CVD but without EDS is questionable 9, 10.…”
Section: Introductionmentioning
confidence: 99%
“…The association with the SAOS was clearly demonstrated; however, in patients with cardiovascular disorders this association proved to be limited. Furthermore, myocardial ischemia or heart failure alone can lead to fatigue and excessive daytime sleepiness, even in the absence of SAOS, and medications for cardiac problems, such as β-blockers, can also lead to excessive daytime sleepiness [29][30][31] . Use of nasoenteric probe in adult emergency service There was a statistically significant association between pulmonary diseases and orotracheal intubation (OTI).…”
Section: Discussionmentioning
confidence: 99%
“…This symptom has been suggested as a risk factor for the aggravation of cardiovascular diseases, still poorly investigated in clinical evaluations in conjunction with other factors, (6,13) and the results of this study corroborate these findings. It is noteworthy that in longitudinal studies, the authors showed that subjects with excessive daytime sleepiness were at increased risk for cardiovascular diseases (14,20) and AMI. (6) The scores obtained in the Epworth Sleepiness Scale were higher for males and the age group of 60 years or older, which is similar to the results found in other studies, (6,(21)(22)(23) though not reaching statistical significance.…”
Section: Discussionmentioning
confidence: 99%
“…(3) It is defined as the increased propensity to sleep in circumstances deemed inappropriate, (9) needing naps during the day. (10) Studies show the association of excessive daytime sleepiness with cardiovascular events, (3,(10)(11)(12)(13)(14) resulting in an increase of 33% for the risk of mortality. (6) A screening for the presence of excessive daytime sleepiness can contribute to detect individuals at high risk for these diseases.…”
Section: Introductionmentioning
confidence: 99%